BIBLIOMETRIC STUDY OF TECHNOPRENEURSHIP (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to conduct a bibliometric analysis of technopreneurship in the form of how many researches on technopreneurship, what studies are discussed the most in each year, and which countries do the most research. The method used is bibliometric analysis using the help of the PoP application in data collection and the VOSViewer application in visualizing the data. This study uses data taken from 2017-2022 with a total of 252 articles. The most widely discussed studies consist of 3, namely Technopreneuship, Development and Study, the country that examines Technopreneurship, namely Indonesia